Green productivity: growth in harmony with nature - Khader, S.A. (2003)
The technological revolutions continue to transform the work methods and processes and quality of life, and inturn, the households as well as societal environment. The latest revolution being the micro-electronics or IT, it has totally redefined the working systems and made one to realize the dreams of a global village in India. - Reproduced.
Keywords: Quality of life